Should I Trust Social Media? How Media Credibility and Language Affect False Memory - Maulina, Dewi; Hakim, Ishaq Mahmudil; Arasy, Ladayna Nurul; Millatina, Marsa Dhiya; Siregar, Ermanda Saskia (Jurnal Psikologi, 2020)
This study examined the influence of credibility and .language in Internet-based media on false memory. A randomized factorial 2 (media credibility) Ã— 2 (language) experimental design was conducted with 106 college students. The two groups of media credibility consisted of social media (LINE) and non-social media (detik.com), while media language consisted of formal and informal language. A confidence test was used to measure false memory. A two-factor ANOVA showed that media credibility significantly affects false memory. Participants in the detik.com group were more confident in the information received and had greater false memory than the LINE group. However, no significant effect of language was found, and no significant interaction effect between media credibility and language on false memory was found. This study suggests that individuals should be cautious when reading information on non-social media platforms, as individuals tend to place more confidence on the source, leading to greater false memory.